If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + (x + 2) + (x + 4) + (x + 6) + (x + 8) = 435 Reorder the terms: x + (2 + x) + (x + 4) + (x + 6) + (x + 8) = 435 Remove parenthesis around (2 + x) x + 2 + x + (x + 4) + (x + 6) + (x + 8) = 435 Reorder the terms: x + 2 + x + (4 + x) + (x + 6) + (x + 8) = 435 Remove parenthesis around (4 + x) x + 2 + x + 4 + x + (x + 6) + (x + 8) = 435 Reorder the terms: x + 2 + x + 4 + x + (6 + x) + (x + 8) = 435 Remove parenthesis around (6 + x) x + 2 + x + 4 + x + 6 + x + (x + 8) = 435 Reorder the terms: x + 2 + x + 4 + x + 6 + x + (8 + x) = 435 Remove parenthesis around (8 + x) x + 2 + x + 4 + x + 6 + x + 8 + x = 435 Reorder the terms: 2 + 4 + 6 + 8 + x + x + x + x + x = 435 Combine like terms: 2 + 4 = 6 6 + 6 + 8 + x + x + x + x + x = 435 Combine like terms: 6 + 6 = 12 12 + 8 + x + x + x + x + x = 435 Combine like terms: 12 + 8 = 20 20 + x + x + x + x + x = 435 Combine like terms: x + x = 2x 20 + 2x + x + x + x = 435 Combine like terms: 2x + x = 3x 20 + 3x + x + x = 435 Combine like terms: 3x + x = 4x 20 + 4x + x = 435 Combine like terms: 4x + x = 5x 20 + 5x = 435 Solving 20 + 5x = 435 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-20' to each side of the equation. 20 + -20 + 5x = 435 + -20 Combine like terms: 20 + -20 = 0 0 + 5x = 435 + -20 5x = 435 + -20 Combine like terms: 435 + -20 = 415 5x = 415 Divide each side by '5'. x = 83 Simplifying x = 83
| 9x^2-3x-11=0 | | x+(x+2)+(x+4)+(x+6)+(x+8)=140 | | Y=20000+.3 | | 24-a=-15 | | Y=2000+.3 | | X^3-3xy+2y^2=0 | | 5y+2=-8y-11 | | 2(3x-4)+7=-4(3x-2) | | 787.5+4.9x=875+3.5x | | (u-8)*10=18 | | 1000x=281421906 | | b+2b+3b-22=4(b+6) | | -26=13t | | -16=6x-1 | | -6v+4(v+3)=-4 | | 400x=1000 | | 7a^2-42=35a | | 33=y+16 | | 12x^3+68x^2+84x= | | 5(n-3)=7+3m | | (6x-3-4)=(4x+14) | | 2x+32+x^2=80 | | 28*60=14x | | 125x-8x^4= | | 42=4n-7(n-9) | | 2x-22=-8 | | (6x-34)=(4x+14) | | x^3+4*x^2+6x+1=0 | | 2x+2x+(x+10)+50=40 | | (q-8)*5=10 | | 11x-18y=8 | | 6x*ln(x^3)=0 |